The role of oral health care professionals in preventing and managing obesity: A systematic review of current practices and perceived barriers. Issue 3 (May 2019) - Arora, Amit; Poudel, Prakash; Manohar, Narendar; Bhole, Sameer; Baur, Louise A
Abstract: Introduction: There is a growing interest to expand the role of oral health care professionals in obesity prevention and management. The aim of this systematic review was to synthesise the evidence on current practices of, and perceived barriers to, oral health care professionals' involvement in obesity screening and management. Methods: Key search strings were developed and used in seven databases from inception through February 6, 2019. Data were screened against inclusion criteria, independently extracted, and quality appraised by two reviewers based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results: Ten studies were included in this review. The practices of oral health care professionals in relation to obesity assessment, counseling, and specialist referrals were found to be very limited. Oral health care professionals believed in their role to support patients for achieving weight-loss goals, however just over one-third were trained in anthropometry. Perceived barriers included lack of time, limited knowledge or training, patients' unwillingness to listen to oral health care professionals' advice, and lack of appropriate specialist referrals. Conclusion: Oral health care professionals are well-positioned and supportive in undertaking healthy weight interventions in their clinical practice; however, their practices are limited due to barriers such as lack of time, limited training and lack of referrals.